Multiagent approach to temporal and punctual urban redevelopment in dynamic, informal contexts. (September 2018) - Patt, Trevor Ryan
This article presents design research speculating on computationally enabled planning approaches for urban sites where informal developments make conventional masterplans ineffectual. The project advances the thesis that the spatial complexity of urban sites can be effectively studied through a network or mesh representation and that rapid change in informal settlements is not an obstacle to planned redevelopment but can be addressed through dynamic modeling and punctual interventions. In this way, the rapid turnover of the built environment can be a mechanism through which to introduce directed planning without canceling out bottom-up actions. In the case study presented, we use a multiagent approach that is able to adapt to a continuously changing context. The agents are driven by weighted random walks and compute localized analyses of the morphology of the network of public space as they move. The information generated by the multiagent simulation is aggregated to identify potential modifications to the urban fabric, with an emphasis on pedestrian connectivity.